The geological and geochemical characteristics of soil on Ore deposits, Itagunmodi gold deposits as a case study (2011)
This work examines the geological and geochemical characteristics of soil on Ore deposits on the formation and maturity of (SHDG) deposits in Itagunmodi, Osun State, Nigeria. Although, some investigations have been carried out on their geological and geochemical characteristics in general, most of the studies are based on limited database. The source and the nature of the gold in the deposits are still not clear. The major objective of this study is to determine the geochemical characteristics of host soil. The plots of major elements collected from five different locations in the mining areas named A-E and three locations outside the mining areas F-H shows that the concentrations of the element is higher within the mining site than area outside the mining site.